Relationship Between Functional Independence and Fall Risk in Indonesian Community-Dwelling Elderly - Djusmadi Rasyid; Anshar Rante; Warda Warda; Ismunandar Ismunandar; Hardianto Dg. Salimung (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Falls among older adults remain a leading cause of injury and loss of independence worldwide. Early detection of functional decline is essential to prevent fall-related complications. This study aimed to examine the correlation between functional independence and fall risk among older adults by employing the Barthel Index and the Timed Up and Go Test (TUGT). Given projections that the global elderly population will surpass 2 billion by 2050, these findings emphasize the importance of integrating functional independence screening into community-based fall prevention programs. Methods: This observational analytical study with a cross-sectional design was conducted in Saronda Village, North Sulawesi, Indonesia, involving 32 community-dwelling elderly aged 60 years and above. Functional independence was assessed using the Barthel Index, while fall risk was evaluated with the TUGT. Data were analyzed using the Spearman rank correlation test. Ethical approval was obtained from the Health Research Ethics Committee of STIKES Kamus Arunika, and all participants provided informed consent. Results: The majority of participants (56.25%) demonstrated functional independence; however, 59.38% were identified as having a high fall risk. Statistical analysis revealed a significant negative correlation between Barthel Index scores and TUGT completion time (r = –0.904; p < 0.001), indicating that higher functional independence was associated with lower fall risk. Conclusion: Greater functional independence is significantly associated with a reduced risk of falls among elderly. These findings highlight the importance of regular functional assessments using the Barthel Index and TUGT as practical tools for early identification of fall risk and for guiding gerontological nursing interventions in community settings.